Elucidation of the effects of trans/cis-isomerization of the cinnamate ligand on the structural, spectroscopic and magnetic properties of cobalt(II) single-molecule magnets - Halaš, Petr; Nemec, Ivan; Čižmár, Erik; Herchel, Radovan (Dalton transactions (Cambridge, England, 2025)
Two new pseudo-octahedral Co(II) complexes 1 [Co(neo)2(trans-cin)]ClO4 and 2 [Co(neo)2(cis-cin)]ClO4 with trans and cis-cinnamic acid (Hcin) and neocuproine (neo) as ligands were prepared. Both complexes were characterized via single-crystal X-ray analysis, infrared spectroscopy, magnetic measurements, and EPR spectroscopy. DC magnetic susceptibility measurements revealed large axial magnetic anisotropy with axial zero-field splitting (ZFS) parameters D = 49.9 and 59.5 cm-1 and rhombicity E/D = 0.307 and 0.147 for 1 and 2, respectively. These results were in accordance with CASSCF/NEVPT2 calculations. AC magnetic data showed the presence of slow relaxation of magnetization for both compounds in the applied DC field. UV irradiation studies in solution show that the complexes most likely undergo trans/cis photoisomerisation, which is, however, accompanied by side reactions and degradation. This was elucidated further utilizing DFT and TD-DFT calculations.